Engineering of diseased human skin equivalent using 3D cell printing for representing pathophysiological hallmarks of type 2 diabetes in vitro. (May 2021) - Kim, Byoung Soo; Ahn, Minjun; Cho, Won-Woo; Gao, Ge; Jang, Jinah; Cho, Dong-Woo
Abstract: Despite many significant advances in 3D cell printing for skin, a disease model displaying the pathological processes present in the native skin has not been reported yet. Therefore, we were motivated for modeling a 3D diseased skin tissue with pathophysiological hallmarks of type 2 diabetes in vitro based on 3D cell printing technique. By stimulating epidermal-dermal intercellular crosstalk found in the native skin, it was hypothesized that normal keratinocytes would be differentiated as diabetic epidermis when interacting with the diabetic dermal compartment. To prove this, a novel wounded skin model was successfully devised during tissue maturation in vitro . Interestingly, the slow re-epithelization was observed in our diabetic model, which is a representative hallmark of diabetic skin. Using the versatility of 3D cell printing, the structural similarities and diabetic properties of the model were further augmented by addition of perfusable vascularized diabetic hypodermis. Insulin resistance, adipocyte hypertrophy, inflammatory reactions, and vascular dysfunction, as the typical hallmarks in diabetes, were found under hyperglycemia. Finally, the feasibility of this new disease model for drug development was successfully demonstrated through application of test drugs. We trust that this study provides a pioneering step towards 3D cell printing-based in vitro skin disease modeling.